Feasible or foolish: Attempting restoration of a Parthenium hysterophorus invaded savanna using perennial grass seed. (15th February 2021) - Cowie, Blair W.; Byrne, Marcus J.; Witkowski, Ed T.F.
Abstract: The annual herb Parthenium hysterophorus L. (Asteraceae), remains one of Southern Africa's most significant invasive weeds, commonly invading savannas, and their rangelands, causing severe losses to agriculture, livestock production and native biodiversity. Previous studies have suggested that perennial grasses may act as useful competitive species, capable of suppressing the growth and invasion of P. hysterophorus . To explore this, a total of 48 plots were established within an invaded savanna, using a randomised block design, and included treatments with and without the clearing of P. hysterophorus, as well as with and without the sowing of native perennial grass seed ( Anthephora pubescens, Chloris gayana, Cynodon dactylon, Digitaria eriantha, Eragrostis curvula, Panicum maximum and Themeda triandra ). Plots were assessed yearly in terms of P. hysterophorus density and growth as well as grass species composition, basal cover, and biomass over a three-year period. Clearing alone was found to exacerbate invasion, increasing P. hysterophorus density by 40%. Whereas the sowing of grass seed, in both the cleared and uncleared plots, increased the abundance of perennial grass species by 28%, subsequently reducing the size, reproductive output and density of P. hysterophorus over the three years. In addition, these sowing efforts contributed towards partial restoration of the plots, enhancing grass basal cover by 15% and biomass production by 17%. Overall, this research suggests that sowing of native grass species, with or without clearing, may be a useful supplementary control or restoration tool towards the long-term management of P. hysterophorus invasions in managed savannas and rangelands in Southern Africa. Highlights: Increased basal grass cover and biomass occurred in plots sown with native grass seed. Sowing of native grass seed suppressed the density of P. hysterophorus by up to 30%. Clearing efforts used alone, detrimentally enhanced P. hysterophorus invasion by 40%. Native grass seed may be a viable restoration tool for invaded savannas / rangelands.